Optimizing Customer Satisfaction: Unveiling the Impact of ARIS Tool Implementation - Rindu Yuna Putri; Togar Alam Napitupulu (Jurnal Mirai Management, 2023)
The development of Information Systems and Information Technology in a fast time makes companies mutually competitive by using the implementation of Information Technology. PT.XYZ is a company that runs an integrated energy business from upstream to downstream. In its capacity as a holding company in the energy sector according to the decree of the Minister of SOE dated June 12, 2020, in general, the business focus of PT.XYZ is carrying out portfolio management activities and business synergies throughout PT.XYZ group, accelerate new business development, as well as run national programs. The method used in the analysis of this case study is the model of Delone and McLean modicfied with TAM model.Respondents of this study consisted of 270 people with the condition of having used the ARIS application.Data testing will be performed using SMART-PLS.This analysis was conducted to measure how much the level of user satisfaction ARIS application. Based on data collection techniques, this study is a descriptive quantitative research. Variables used in this study are System Quality,Information Quality,Service Quality,Perceived Usefulness,and Perceived Ease of Use.The results of this study are Information Quality and Service Quality has a positive effect on user satisfaction. Keywords: IS Success Model, TAM, ARIS, User Satisfaction